Assessment of Organ Donation Knowledge and Attitudes Among Patients Visiting the Nephrology Outpatient Clinic at a Tertiary Healthcare Facility - Yarasir, Ezgi; Gomleksiz, Mehtap; Gomleksiz, Muhammet Ridvan; Dogukan, Ayhan (Sage Publications Inc, 2025)
This study aims to assess the knowledge levels, attitudes, and influencing factors related to organ donation among patients who visited the Nephrology outpatient clinic. This descriptive and cross-sectional research had 269 participants. Research data were collected utilizing a three-part questionnaire. The first part of the questionnaire comprised the Sociodemographic Information Form, the second part evaluated knowledge about organ donation, and the final section included the Organ Donation Attitude Scale. The mean age of the participants was 43.7 +/- 17.1 years, and 55.8% of them were women. A total of 37.5% of the participants stated that they were considering organ donation. Participants with a high school education or higher, those who believed they had sufficient knowledge about organ donation, and those who had a family member awaiting organ transplantation demonstrated a positive attitude toward organ donation (p < .05). Understanding societal knowledge and attitudes about organ donation is crucial for assessing individual awareness of this issue.
Keywords: organ donation; knowledge level; attitude; organ transplantation